Paradigma Misi dalam Syair Lagu Kolose Terhadap Pluralisme Keallahan Postmodern - Nathalia Kenny Merian Mamonto; Aji Suseno (APOSTOLOS, 2022)
: Great Commission that should be the responsibility of believers becomes irrelevant in the midst of the challenges of post-modern era where everything is relative. The mission paradigm in this era began to shift, which all were motivated by post-modern culture. In this relative era, digital acceleration can directly make Christians facing global culture of the world that focuses on the universal view which state that Jesus is not the only way to salvation but one of the ways to salvation. This is because the post-modern paradigm of thinking concerning religion is no longer talking about truth but about what does someone want. Of course this is contrary to Christianity which states that Jesus is the final and the only way of salvation. This study uses a qualitative research with a descriptive approach to find out the truth in Paul’s writings in the Colossian Song which describe the pre-existence of Christ. In Paul’s writings especially in Colossians 1:15-20, is a quote from the early church confession that Paul took and used it to show about Christ who is the only God.